Enhanced Grain Size and Crystallinity in CH3NH3PbI3 Perovskite Films by Metal Additives to the Single-Step Solution Fabrication Process. (30th April 2018) - Almutawah, Zahrah S.; Watthage, Suneth C.; Song, Zhaoning; Ahangharnejhad, Ramez H.; Subedi, Kamala K.; Shrestha, Niraj; Phillips, Adam B.; Yan, Yanfa; Ellingson, Randy J.; Heben, Michael J.
ABSTRACT: Methods of obtaining large grain size and high crystallinity in absorber materials play an important role in fabrication of high-performance methylammonium lead iodide (MAPbI3 ) perovskite solar cells. Here we study the effect of adding small concentrations of Cd 2+, Zn 2+, and Fe 2+ salts to the perovskite precursor solution used in the single-step solution fabrication process. Enhanced grain size and crystallinity in MAPbI3 films were obtained by using 0.1% of Cd 2+ or Zn 2+ in the precursor solution. Consequently, solar cells constructed with Cd- and Zn-doped perovskite films show a significant improvement in device performance. These results suggest that the process may be an effective and facile method to fabricate high-efficiency perovskite photovoltaic devices.